PENGARUH SUPERVISI AKADEMIK DAN IKLIM SEKOLAH TERHADAP KOMPETENSI PEDAGOGIK GURU PAI SD DI KOTA BENGKULU - Muhammad Nuraini (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2016)
This study aims to determine the influence of academic supervision and school climate for pedagogical competence Islamic religious education teacher primary schools in the city of Bengkulu , amounting to 235 teachers. Because a large number of population on the basis of suggestions Roscoe ( Member sampled a minimum of ten times the number of variables ) and with a simple random sampling technique determined the size of the sample 45 teachers. Data were collected through questionnaires answered directly by teachers, then analyzed statistically by using multiple regression analysis using SPSS software version is twenty-one for the window.Regression analysis showed that: (1) the influence of academic supervision (X1) with pedagogical competence (Y) gives the figure of 5.159 t observation> 1.675 (t table) means the value of academic supervision (X1) influence the pedagogic competence (Y), big effect that is equal to 0.473 means that the amount of variant pedagogical influenced academic supervision by 47.3%, (2) the influence of the school climate (X2) gives the figure of 2,481 t observation> 1.675 (t table) means the value of school climate (X2) effect on pedagogical competence (Y) big influence in the amount of 0.192 means that the amount of variant pedagogical school climate influenced by 19.2%, and (3) test the influence of academic supervision (X1) and school climate (X2) to pedagogical (Y) of Anova obtained F count equal to 19.294 with a significance level F table (19.294> 1.865) means the statistical data used to prove that all the independent variables (academic supervision and climate school) influence on pedagogical competence. Or in other words the academic supervision (X1), school climate (X2) together influence the pedagogical competence (Y).